Analysis of concrete characteristics with the replacement of natural fine aggregate by industrial solid waste - Alves dos Santos Costa, Marcus Luiz; Pereira Valões, Débora Cristina; Gomes Do Nascimento, Carlos Fernando; Da Silva Lima, Everton Gustavo; Ribeiro Da Silva, Gustavo; Santos Da Silva , Thais Tainan; Santos, Thiago Sette (Revista ALCONPAT, 2022)
The objective of this study includes the use of solid industrial waste to improve the mechanical properties of cementitious composites. To this end, the incorporation of granite gravel dust and marble dust in the manufacture of cement-based composites was evaluated, partially replacing the natural fine aggregate at levels of 50% and 100%. For this, characterization tests of the aggregates were performed, besides the evaluation of the axial compressive strength of the specimens. The results showed that the mixtures containing 50% recycled aggregate gave the material a compressive strength of 29.09 MPa, i.e., 4% higher when compared to the reference mixtures, making the results satisfactory, demonstrating the feasibility of recycled aggregates in concrete pieces.